Noce i dnie Marii Dąbrowskiej po słoweńsku – problemy translacji - Ostromęcka-Frączak, Bożena (Acta Universitatis Lodziensis. Folia Linguistica, 1995)
The author discusses the successive translations of Maria Dąbrowska’s works into Slovenian. They comprise one novel - Noce i dnie, and four short stories: Jesionka, Zdobycie serc, Dziecko, and Pocieszenie. The analysis of the language of translation concentrates on Noce i dnie. The author is interested in two problems: In what ways does the translation reflect the Polish ciuntryside and town reality, and to what extent does it reflect the language stylization of the novel. She concludes that F. Vodnik resorted in his translation to tabooization and neutralization of Maria Dąbrowska’s text, erasing in this way the historic colour of Noce i dnie. Vodnik omits the dialect stylization and the individualization of the characters’ language present in the original. As a result of that, peasants and town workers speak in a similar way. The language of the translation is in most cases normalized and uniform with respect to style. It lacks the old-fashioned mellowness which gives the Polish original an additional charm. Vodnik avoids using expressive words and often „improves” pejorative words, replacing them with the ones less negatively marked or using euphemisms. The above remarks do not, in any way, lower the quality of F. Vodnik’s translation – their only purpose is to draw attention to the difficulties connected with reflecting the style of the translated text. F. Vodnik, not only a translator, but also a good Slovenian writer and poet, did not always manage to deal with them in adequate way. His translation of Noce i dnie has so far been the only translation of the novel into Slovenian. The novels by other writers, e.g. Henryk Sienkiewicz, or Władysław Reymont, have been translated several times by different translators. No translator has undertaken to translate Noce i dnie again, which proves the scale of translation difficulties that any future translator of the novel will have to encounter.